Todas las definiciones son un promedio (2017)
A friend once gave me a cartridge belt that read "Art is more important than math". My first reaction was to write with a "not" marker between "is" and "more". However, the fundamental question was what is "art" and what is "math". The exercise of defining any of the two words is to average conceptions and in this way to restrict. Generally, when asked what art is, most people seek to relate it to techniques such as painting or sculpting, or to concepts such as what is beautiful or aesthetic (whatever that means); However, in the effort of humanity to develop a sense of individual identity, we have begun to confuse even our own definitions. Usually, people associate mathematics with statistics, engineering, science, and restrict their definition of use, excluding everyday life and its wide implementation possibilities.